PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GI TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Seri Rahayu Latmawati; Zubaidah Zubaidah; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThe problem of this research was students’ learning outcomes of SMPN 1 Sungai Raya that below than the standard score,especially in probability topic. This research aimed to know the effect of cooperative learning model with group investigation type on students’ learning outcomes in probability topic. The form of this research was experiment and research design was post test only control group design. The samples of this research were 31 students of IX I class and 30 students of IX K class of SMPN 1 Sungai Raya.Essay questions was used to collecting the students’ learning outcomes. The result of this research showed that the average of posttest score of the experiment class was 12,63 and the average of posttest score of the control class was 10,97. Hypothesis was tested using U Mann-Whitney test showed that the result of Sig <  , is 0,039 < 0,05. The H0 was rejected and Ha was accepted, because sig < . It could be concluded that there was significant result of students’ learning outcomes between students had been given treatment using cooperative learning model with group investigations type and students had been given direct teaching model in probability topic. Keywords: Cooperative Learning, Group Investigation,  Learning Outcomes, Mathematics